Influence of Vitrification Device, Warming Protocol, and Subsequent In Vitro Culture on Structural Integrity of Testicular Fragments from Adult Domestic Cats - Macente, Beatrice Ingrid; Fonseca-Alves, Carlos Eduardo [UNESP]; Magalhaes, Georgia Mode; Tavares, Mariana Riboli [UNESP]; Mansano, Cleber Fernando Menegasso; Mouttham, Lara; Apparicio, Maricy [UNESP]; Toniollo, Gilson Helio [UNESP]; Comizzoli, Pierre (Mary Ann Liebert, Inc, 2022)
The objective of the study was to evaluate the integrity of cat testicular tissues after vitrification with different devices followed by different warming conditions. The influence of vitro culture for 24 hours after warming also was examined. Testicular tissues from adult domestic cats were dissected in small fragments that were vitrified using Cryotop(R) or threaded on fine needles, warmed (directly at 37 degrees C or with a preliminary 10 seconds exposure to 50 degrees C), and/or cultured in vitro for an additional 24 hours. For each treatment group, tissues were assessed based on histology, apoptosis, and sperm DNA integrity. Results showed that fragments of testicular tissues were efficiently cryopreserved (maintaining the quality of all cell types) with vitrification with Cryotop followed by direct warming at 37 degrees C, and additional culture of 24 hours at 38.5 degrees C. These encouraging results are paving the road to optimize preservation protocols and use them for systematic banking of tissues from genetically valuable felids.
Keywords: testicular tissue; domestic cat; vitrification; cryodevice; structural integrity